Implementasi Pendidikan Karakter di Sekolah Dasar Melalui Pembelajaran Kewarganegaraan - Wahyu Putri Bunda; Rendy Rahmadani Saputra; M. Desyrizal Pratama; Ilham Hudi; Salsa Sabila (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
In elementary school, Citizenship Education subjects are an ideal forum for inserting character education, because the topics include values ​​such as responsibility, honesty, justice, cooperation and love of the country. Teachers are able to integrate various activities and learning methods to help students know and apply these values ​​in everyday life. In this study, the researcher used a qualitative or narrative method which aims to study a problem more deeply using the method of analyzing several theories without calculating percentages. This research uses a qualitative research method because it describes the implementation of character education in elementary schools to see clearly news about the reality that occurs in the field, after that analyzing the results. Therefore, Citizenship Education learning must be improved to improve student character through planning, implementation and assessment processes. This effort is included in the Citizenship Education subject, where citizenship education material produces student character. For this reason, character education is said to have been successfully implemented in several elementary schools. It can be concluded that the implementation of character education through Civics subjects in elementary schools is important, although there are still several challenges such as a lack of teacher training and a rigid curriculum.